Attentional control and learning Another way to look at attention required during learning - Buysse, Alexandre A.J. (Swiss Journal of Educational Research, 2018)
Recent research has stressed the cognitive processes that are not under the attentional control of the learner, especially from a developmental point of view. The regulatory processes that take place without the learner’s conscious knowledge seem to play an important part in his comprehension and in his ability to link newly acquired notions with already mastered concepts. These unconscious regulatory processes are also crucial to problem solving. However, most approaches to teaching require students to focus their attention during classroom practices and ask them to make their solving procedures explicit, as well as practice immediately after knowledge transfer. Based on our researches, we offer a conceptualization of the relations between regulatory processes and locus of control of regulatory processes. We aim at taking into account a number of known facts about the functioning of the brain and the complexity of the interactions between different loci of control occurring during teaching.